The truth project- paper two- using staff training and consultation to inculcate a testimonial sensibility in non-specialist staff teams working with survivors of child sexual abuse - Barker, Claire; Taggart, Daniel; Gonzalez, Marta; Quail, Sally; Eglinton, Rebekah; Ford, Stephanie; Tantam, William (Frontiers in Psychiatry, 2023)
In Paper One of the Truth Project submission, there was an exploration of how child sexual abuse survivors experienced participation, with a particular emphasis on the project’s capacity to address epistemic relational inequality. In this paper, we explore how trauma informed training and consultation for non-specialist Inquiry staff enabled them to work with survivors in the Truth Project and other areas of the Inquiry. The paper draws on data gathered from 32 semi-structured interviews with a range of Inquiry staff, including civil servants, legal professionals, senior operational managers, and researchers. The interview questions mapped on to the trauma informed principles embedded in the Inquiry and can be considered in the context of the survivor paper. Findings included all staff having an awareness of what it meant to be trauma informed in an Inquiry context, talking about the principles in terms of value-based positions. Staff described an awareness of needing to attend to the idiosyncratic experiences of the individual survivor, and there was recognition that previous damage to survivor trust, through institutional failure, meant that demonstrating trustworthiness was a central task. Staff talked about the impacts of participation on some survivors, and the impacts it had on them to be exposed to trauma-related materials. There was acknowledgment of the limitations of the trauma informed approach but also recognition of the wider applications of this learning for other areas of their personal and professional lives. There is some support for the therapeutic culture developed at the Inquiry leading to what Fricker refers to as a testimonial sensibility, a quality of listening necessary for the establishment of epistemic justice. The discussion focuses on how this way of working can be applied to other public service settings and how epistemic justice concepts can be included in more traditional trauma informed care models to encourage an ethic of listening that has political and social, in addition to therapeutic, outcomes.